2013
DOI: 10.1134/s1062739149020172
|View full text |Cite
|
Sign up to set email alerts
|

Emergency control of technological environment and electric machinery activity in coal mines

Abstract: The authors develop standards and design of pre-emergency, emergency and post-emergency control of mine technological environment and electric machinery activity. The electric machinery operation parameters to be controlled are energy supply of explosion-proof electric machinery, cable integrity and improper access to the machinery; the control objects are switchers and starters within an extraction district. The technological environment parameters to be controlled are gas content, including CH 4 , CO, CO 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…[4][5][6] From the analysis of these factors, it can be concluded that it is necessary to significantly improve the efficiency of the safety system in underground coal mines. [7][8][9][10][11][12] The improvement of the security system is achieved by establishing adequate communications between control rooms and underground workplaces [13][14][15][16] ; by establishing effective environmental monitoring [17][18][19] ; by applying different methods of automation of production and transport 20,21 and significant application of ergonomic principles in the analysis of human activities in this field. [22][23][24] Analysis of the activities of operators in control rooms of a coal mine is very important to achieve optimal performance of the management system.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] From the analysis of these factors, it can be concluded that it is necessary to significantly improve the efficiency of the safety system in underground coal mines. [7][8][9][10][11][12] The improvement of the security system is achieved by establishing adequate communications between control rooms and underground workplaces [13][14][15][16] ; by establishing effective environmental monitoring [17][18][19] ; by applying different methods of automation of production and transport 20,21 and significant application of ergonomic principles in the analysis of human activities in this field. [22][23][24] Analysis of the activities of operators in control rooms of a coal mine is very important to achieve optimal performance of the management system.…”
Section: Introductionmentioning
confidence: 99%
“…Mining operations stability is also greatly affected by severe operating conditions including extreme seasonal variations in temperature, various types of precipitation throughout a year, vibration, dustiness and etc. In this regard active research and pilot studies are currently in progress to work out various remote monitoring systems which allow monitoring of power consumption trends and operating conditions of electric equipment for surface and underground mining, including start-control devices, generators, electric motors, their emergency protection and control systems [1], [2], [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Therefore, the emergency control of technological environment and robust software control of the electric machinery activity in coal mines are needed. 35,36…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Therefore, the emergency control of technological environment and robust software control of the electric machinery activity in coal mines are needed. 35,36 The next step in the development of CIS in underground coal mines is the introduction of teleremote systems. 37 The introduction of these systems can provide significant improvement in mine production performance and safety of workers who are removed from the most dangerous locations in the pit during the extraction of coal.…”
Section: Introductionmentioning
confidence: 99%